Hubungan antara ketepatan waktu pemberian makanan pendamping ASI dengan status gizi balita di Kabupaten Bolaang Mongondow Timur - Tampi, Elshadai; Kawengian, Shirley Everdina Susanna; Bolang, Alexander Sam Leonard (UNIVERSITAS SAM RATULANGI, 2024)
Background: Inadequate nutritional status in toddlers is one of the serious challenges in the effort to achieve sustainable development goals in many countries, including Indonesia. Data from Riskesdas revealed the prevalence of toddlers aged 0-59 months based on the BB/U index in 2018 in North Sulawesi Province, there were 4.21% cases of malnutrition and 11.23% cases of undernutrition. In addition, based on the TB/U index, 9.77% of toddlers experience significant growth delays and 15.69% have short height. Based on the BB/TB index, 2.86% of toddlers are categorized as very thin and 6.67% are underweight. Aim: To determine the relationship between complementary feeding (MP-ASI) and the nutritional status of toddlers in East Bolaaang Mongondow District. Methods: This study is an analytical survey research using secondary data from the 2021 Indonesian Nutritional Status Survey (SSGI) data. Results: Analysis using chi-square statistical test based on BB/U value p=0.758, TB/U value p=1.00, and BB/TB value p=1.00. Conclusion: There is no relationship between MP-ASI and nutritional status based on BB/U, TB/U, and BB/TB. Keywords: complementary feeding, nutritional status, toddler.